The last things : resurrection, judgment, glory - Bloesch, Donald G., 1928-2010. (Downers Grove, Ill. : InterVarsity Press, 2004)
"Besides contributing to late modern evangelical theology, Christian Foundations will be of value to reflective Christians who wonder what ancient faith has to say to perplexing new times. It will be of special help to students who want to hold to orthodoxy but honestly engage contemporary thought."--BOOK JACKET.
1. Introduction -- 2. Controversial themes in eschatology -- 3. Light against darkness -- 4. The day of the Lord -- 5. The millennial hope -- 6. The resurrection of the dead -- 7. The interim state -- 8. The communion of saints -- 9. Predestined to glory -- 10. Israel's salvation : the supersessionist controversy -- 11. The triumph of grace -- 12. The dawning of hope.
Includes bibliographical references (p. 303-323) and index.
Keywords: Eschatology